Rapture fiction and the evangelical crisis - Gribben, Crawford (Darlington, UK Evangelical Press, 2006)
Includes bibliographical references.
Keywords: LaHaye, Tim F. Left behind series; Bible -- Prophecies -- End of the world -- History and criticism; Rapture (Christian eschatology) -- Biblical teaching; Rapture fiction -- critique